Empati dalam Perspektif Hadis - Nurjaman Nurjaman; Muhammad Alif (Reflection : Islamic Education Journal, 2025)
Empathy is generally understood as the ability to feel and understand the feelings of others, the nature of empathy is very necessary and very crucial in Islamic social ethics and morality. In the treasury of Islam, the hadith of the Prophet Muhammad SWT is the second source of teachings after the Qur'an playing a central role in shaping the understanding of human values, including empathy. This study focuses on the analysis of the position and teaching of empathy in the hadiths of the Prophet, as well as its impact on the formation of Muslim social character. Using qualitative methods and literature studies, this study analyzes hadiths that clearly or implicitly convey messages of empathy. The findings of the study show that in the hadith, empathy is not just an emotional response, but a manifestation of moral responsibility that is manifested through compassion, justice, solidarity, and concern for others. Thus, the hadiths of the Prophet become a normative basis that emphasizes the significance of empathy as the main pillar in realizing a civilized and just Islamic society.